2016
DOI: 10.1016/j.molp.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT-I Component VPS23A Affects ABA Signaling by Recognizing ABA Receptors for Endosomal Degradation

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.All studies published in MOLECULAR PLANT are embarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
114
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 62 publications
1
114
0
6
Order By: Relevance
“…The ELC/AtVPS23A ESCRT-I component also binds Ub in vitro (Spitzer et al, 2006). Interestingly, ELC/ AtVPS23A and AtFYVE1 directly bind to the AtPYL4 abscisic acid (ABA) receptor and AtIRT1, two ubiquitinated endocytosed cargos (Barberon et al, 2014;Belda-Palazon et al, 2016;Yu et al, 2016). Consistently, genetic interference with ELC/AtVPS23A or AtFYVE1 expression yields ubiquitinated protein accumulation in (Zhou et al, 2013), sequestration of anthocyanins in the vacuole (Pourcel et al, 2010), chlorophagy of physiological and damaged chloroplasts (Izumi et al, 2017), reticulophagy (Liu et al, 2012), pexophagy (Shibata et al, 2013), mitophagy (Li et al, 2014) and xenophagy (Hafren et al, 2017).…”
Section: Dual Role Of K63-linked Chains In Plant Endocytosismentioning
confidence: 86%
See 2 more Smart Citations
“…The ELC/AtVPS23A ESCRT-I component also binds Ub in vitro (Spitzer et al, 2006). Interestingly, ELC/ AtVPS23A and AtFYVE1 directly bind to the AtPYL4 abscisic acid (ABA) receptor and AtIRT1, two ubiquitinated endocytosed cargos (Barberon et al, 2014;Belda-Palazon et al, 2016;Yu et al, 2016). Consistently, genetic interference with ELC/AtVPS23A or AtFYVE1 expression yields ubiquitinated protein accumulation in (Zhou et al, 2013), sequestration of anthocyanins in the vacuole (Pourcel et al, 2010), chlorophagy of physiological and damaged chloroplasts (Izumi et al, 2017), reticulophagy (Liu et al, 2012), pexophagy (Shibata et al, 2013), mitophagy (Li et al, 2014) and xenophagy (Hafren et al, 2017).…”
Section: Dual Role Of K63-linked Chains In Plant Endocytosismentioning
confidence: 86%
“…A limited number of integral or associated plasma membrane proteins are known to be ubiquitinated in vivo, carrying either multi-monoUb and/or K63-linked chains (Barberon et al, 2011;Kasai et al, 2011;Roberts et al, 2011;Leitner et al, 2012;Lin et al, 2013;Bueso et al, 2014;Yu et al, 2016). The use of a K63 polyUb-specific sensor coupled to proteomics greatly enhanced the repertoire of plasma membrane proteins conjugated with K63-linked chains (Johnson & Vert, 2016).…”
Section: Dual Role Of K63-linked Chains In Plant Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…So far, two main types of negative feedback regulatory loops of ABA signalling have been identified: the ubiquitin‐mediated proteasomal degradation of ABA key central regulators and the expressional regulation of the key central regulators genes. E3 ligases such as KEG, DWA1, and DWA2 target ABF/AREB/ABI5‐type bZIP transcription factors for proteasomal degradation (Chen, Liu, Stone, & Callis, ; Lee, Kang, et al, ; Liu & Stone, , ; Stone, Williams, Farmer, Vierstra, & Callis, ), whereas E2 ligase VPS23A and E3 ligases CUL4 and RSL1 promote the proteasomal degradation of PYR/PYL/RCABR receptors (Belda‐Palazon et al, ; Bueso et al, ; Seo et al, ; Yu et al, ). E3 ligases PUB12 and PUB13 target PP2C proteins, but only when they interact with ABA receptors (Kong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane‐localized auxin efflux carrier PIN2 (Spitzer et al ) and Brassinosteroid receptor BRI1 (Martins et al ) have been reported to be PVC cargo proteins, and are sorted for vacuolar degradation by the ESCRT system. Although the ESCRT pathway has long been considered specifically to be targeting integral membrane proteins, recent studies have demonstrated that non‐integral membrane proteins, such as the Arabidopsis ABA receptor PYR1‐LIKE 4 (PYL4), also employ ESCRT machinery components FYVE1 and VPS23A for endosomal sorting (Belda‐Palazon et al ; Yu et al ).…”
Section: Introductionmentioning
confidence: 99%